Correlation between Increased Serum Vascular Endothelial Growth Factor Levels and 30-Day-Outcome After Acute Myocardial Infarction - Sylvia Youvella; Adi Koesoema Aman; Nizam Akbar (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2021)
Vascular Endothelial Growth Factor (VEGF) plays an important role in the process of regeneration and vascular repair. Atherogenesis and angiogenesis contribute to the formation of coronary collateral circulation as an alternative source of blood supply during the repairing process of Acute Myocardial Infarction (AMI). This study aimed to investigate the elevation of VEGF and its correlation to Peripheral Blood Mononuclear Cells (PBMC) and Major Adverse Cardiovascular st nd th Events (MACE). Serum VEGF measurements were carried out on 1 , 2 , and the 5 -day onset of angina on 20 patients using st th Chemwell Analyzer based on ELISA method. PBMC was counted on days 1 and 5 according to CBC results from Automatic Cell Counter Sysmex XN-1000i. The major adverse cardiovascular event was recorded 30 days after AMI onset. It was found nd that serum VEGF level in this study was 169.3±34.5 pg/mL on the 1st day, 217.0±49.7 pg/mL on the 2 day, and th th 249.2±48.5 pg/mL on the 5 day. Serum VEGF levels increased gradually and the highest value was found on the 5 day st (p=0.000). There was no correlation between elevated serum VEGF levels with PBMC on the 1 day (p=0.429, r=-0.035) and th the 5 day of AMI (p=0.225, r=+0.081). There was no correlation between elevated serum VEGF levels with incidence of MACE on 30 days after onset of AMI (OR=0.959, 95% CI, p=0.302). Serum VEGF concentrations are increased in Acute Myocardial Infarction and can be used as a marker of myocardial injury. However, this study was unable to prove its role in the outcome of AMI